2016
DOI: 10.1093/annonc/mdv598
|View full text |Cite
|
Sign up to set email alerts
|

TP53 mutational status is predictive of pazopanib response in advanced sarcomas

Abstract: Mutations in TP53 may serve as a predictive biomarker of response to VEGFR inhibition in patients with advanced sarcoma. Larger, prospective studies are necessary to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 12 publications
1
59
1
Order By: Relevance
“…8 Several recent studies from our group and others have suggested that patients with TP53 mutations may have better outcomes when treated with anti-angiogenesis agents, perhaps because TP53 alterations result in increased VEGF-A levels. [9][10][11][12] We have also reported that patients with TP53 alterations who were treated with anti-VEGF/VEGR agents-with no other matches-had higher rates of response, PFS, and OS compared with patients with wild-type TP53. 12 We therefore performed subanalyses to determine outcomes if groups of matched patients included TP53 matched to VEGF/VEGFR inhibitors (groups 2, 4, and 5; Table 1 and Fig 1).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…8 Several recent studies from our group and others have suggested that patients with TP53 mutations may have better outcomes when treated with anti-angiogenesis agents, perhaps because TP53 alterations result in increased VEGF-A levels. [9][10][11][12] We have also reported that patients with TP53 alterations who were treated with anti-VEGF/VEGR agents-with no other matches-had higher rates of response, PFS, and OS compared with patients with wild-type TP53. 12 We therefore performed subanalyses to determine outcomes if groups of matched patients included TP53 matched to VEGF/VEGFR inhibitors (groups 2, 4, and 5; Table 1 and Fig 1).…”
Section: Discussionmentioning
confidence: 88%
“…A patient's tumor was considered matched with a targeted therapy if a drug was known to inhibit the aberration at low nanomolar concentrations or if an antibody targeted the alteration product, per literature data [9][10][11][12] (Appendix). Subset analyses are listed in Table 1.…”
Section: Definition Of Matched Therapymentioning
confidence: 99%
“…However, the same effect was not seen amongst patients with TP53 wild-type malignancies. In addition, another recent study documents that patients with sarcomas who respond to the VEGFR inhibitor pazopanib harbored TP53 mutations (33). TP53 is also potentially targetable with the WEE1 inhibitor currently in clinical development (AZ1775, NCT01748825) (34).…”
Section: Discussionmentioning
confidence: 99%
“…Our current data support the concept that TP53 status may represent a ready biomarker for response to anti-angiogenesis agents, with multivariate analysis demonstrating significant improvement in all outcome parameters when individuals with TP53-mutant, but not TP53 wildtype, advanced neoplasms were treated with anti-angiogenesis agents. Recently, TP53 mutational status was also shown to be predictive of response to the VEGFR inhibitor pazopanib in advanced sarcomas (45). The underlying mechanism of response may relate to TP53 mutations being associated with upregulation of VEGF-A and VEGFR2 expression (7,(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%